2020
DOI: 10.1111/1759-7714.13563
|View full text |Cite
|
Sign up to set email alerts
|

Impact of previous percutaneous coronary intervention on cardiovascular outcomes and mortality after lung cancer surgery: A nationwide study in Korea

Abstract: Background The number of patients with operable lung cancer with a history of percutaneous coronary intervention (PCI) has increased. However, cardiovascular outcomes and mortality, according to the time from PCI to surgery, and the follow‐up time after surgery are largely unknown. Here, we aimed to compare the cardiovascular outcomes and mortality of these patients with a history of PCI to those of patients without a history of PCI. Methods Using the Korean National Health Insurance Service Database, we selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, guidelines recommend http://www.jchestsurg.org JCS maintaining antiplatelet therapy because thrombotic complications are more serious and can result in long-term sequelae or death. A Korean nationwide study showed that interrupting antiplatelet therapy during pulmonary resection increases the risk of major adverse cardiac events (MACE) [16]. Additionally, interruption of antiplatelet therapy within the first month after percutaneous coronary intervention (PCI) is known to be significantly associated with an increased MACE rate [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, guidelines recommend http://www.jchestsurg.org JCS maintaining antiplatelet therapy because thrombotic complications are more serious and can result in long-term sequelae or death. A Korean nationwide study showed that interrupting antiplatelet therapy during pulmonary resection increases the risk of major adverse cardiac events (MACE) [16]. Additionally, interruption of antiplatelet therapy within the first month after percutaneous coronary intervention (PCI) is known to be significantly associated with an increased MACE rate [17].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these patients should not have a recent history of myocardial cancer infiltration but should have a history of myocardial infarction, PCI failure, or infeasible unstable angina. For patients, particularly those unable to undergo a second operation, the combined procedure is deemed secure, yielding positive outcomes and a favorable prognosis [14,42,[64][65][66].…”
Section: Indications For Simultaneous Operationmentioning
confidence: 99%
“…However, there exists a significant controversy regarding the extent of lymph node dissection. While thorough systematic lymph node dissection is generally deemed beneficial, some studies question the survival advantage compared to more limited dissection [14]. Furthermore, systematic lymph node dissection prolongs operation time and increases the postoperative incidence rate [96].…”
Section: Scope Of Lymph Node Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Video-assisted thoracoscopic surgery (VATS) was preferred for patients with early-stage lung cancer because this minimally invasive surgery can increase long-term survival and reduce complications [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%